2021
DOI: 10.1016/j.ijbiomac.2020.12.224
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin perturbs lipid rafts and requires integrity of Pma1p-lipid rafts association to exert its antifungal activity against Saccharomyces cerevisiae

Abstract: Lactoferrin (Lf) is a bioactive milk-derived protein with remarkable wide-spectrum antifungal activity. To deepen our understanding of the molecular mechanisms underlying Lf cytotoxicity, the role of plasma membrane ergosterol-and sphingolipid-rich lipid rafts and their association with the proton pump Pma1p was explored. Pma1p was previously identified as a Lf-binding protein. Results showed that bovine Lf (bLf) perturbs ergosterol-rich lipid rafts organization by inducing intracellular accumulation of ergost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 66 publications
(104 reference statements)
2
13
0
Order By: Relevance
“…In agreement with this, BafA1 and ammonium chloride, two lysosomotropic agents that inhibit V‐ATPase activity, almost completely reduced the entry of a SARS‐CoV‐2 pseudovirion in cells expressing its receptor 320 . Our studies demonstrating the ability of lactoferrin to inhibit V‐ATPase add this natural protein to the list of anti‐viral agents, which in particular can be explored in the treatment of infections caused by SARS‐CoV‐2 82,102,322 . These examples further highlight the power of modulating V‐ATPase activity for antiviral purposes.…”
Section: Therapeutic Opportunities Based On V‐atpase Activity Modulationsupporting
confidence: 79%
“…In agreement with this, BafA1 and ammonium chloride, two lysosomotropic agents that inhibit V‐ATPase activity, almost completely reduced the entry of a SARS‐CoV‐2 pseudovirion in cells expressing its receptor 320 . Our studies demonstrating the ability of lactoferrin to inhibit V‐ATPase add this natural protein to the list of anti‐viral agents, which in particular can be explored in the treatment of infections caused by SARS‐CoV‐2 82,102,322 . These examples further highlight the power of modulating V‐ATPase activity for antiviral purposes.…”
Section: Therapeutic Opportunities Based On V‐atpase Activity Modulationsupporting
confidence: 79%
“…Based on these studies and our experimental evidence, we propose that failure of Pma1 to oligomerize may trigger the internalization of membrane sections containing incorrectly folded proteins and, consequently, trigger the remaining physiological alterations associated with the disruption of membrane homeostasis. Thus, our findings support the rationale of using Pma1 as a target for designing novel antifungal molecules 3941 . Methotrexate and fluconazole are two molecules that deplete Pma1 in S. cerevisiae , compromising ion transport and the influx of nutrients 29,42 .…”
Section: Discussionsupporting
confidence: 79%
“…48 A recent study revealed that Lf binding protein Pma1p, a proton pump which is inhibited by Lf through interruption of the membrane ergosterol and sphingolipid rich lipid rafts connected with Pma1p, promotes the intracellular accumulation of ergosterol, and it also reduces the V-ATPase activity to stimulate antifungal activity. 49 Furthermore, hLf prevents oral candidiasis caused by C. albicans, via upregulation of anti-inflammatory cytokines…”
Section: Antifungal Activitymentioning
confidence: 99%
“…48 A recent study revealed that Lf binding protein Pma1p, a proton pump which is inhibited by Lf through interruption of the membrane ergosterol and sphingolipid rich lipid rafts connected with Pma1p, promotes the intracellular accumulation of ergosterol, and it also reduces the V-ATPase activity to stimulate antifungal activity. 49 Furthermore, hLf prevents oral candidiasis caused by C. albicans , via upregulation of anti-inflammatory cytokines and downregulation of virulent candida genes. 50 The antifungal drug like fluconazole combined with Lf from various species significantly enhanced the inhibitory effect and decreased the minimum inhibitory concentration (MIC) against Candida species, Saccharomyces cerevisiae , and Cryptococcus neoformans .…”
Section: Health Benefits Of Lactoferrinmentioning
confidence: 99%